ALTERNATIVE ENERGY BIOGAS FROM CHOCOLATE PEEL - Mardhita Arlindawati, Sri redjeki, Dias Asmoro Putra, (Jurnal Teknik Kimia, 2011)
The development of alternative energy fuel technology at present many are produced from biologicalresources, eg the manufacture of biodiesel and biodiesel as a fuel substitute for gasoline. This aims to obtainbiogas that can be used as alternative energy and find operating conditions that produce appropriate levelsof CH4 in the standard Indonesian. The first stage is done by preparing 1 liter of raw materials ie brown rindand water are then mixed with a starter (cow dung) 10% of the volume of raw materials and the addition ofyeast and grass after it is mixed until blended. Then put into containers / bottles that have been fitted hose,water manometer, and the gas holder. The research was done in stages with the conditions that you run.Variables that run is a comparison of raw material (1:1; 1:1.5; 1:2; 1.5:1; 2:1), observation time (5 days, 10days, 15 days, 20 days, 25 days , 30 days), and the variable addition of grass (50 gr, 100 gr, 150 gr, 200 gr).From the results of this study found the greatest level of 74.22% in comparison 1 (water): 1.5 (brown skin)with the addition of 150 g of grass while low levels of 60.04% in comparison 2 (water): 1 (brown skin ) withthe addition of 200 g of grass, the results of this study meets the National Standards of Indonesia.Key words: Biogas, grass, yeast